Instrumento De Evaluación De La Competencia En Literacia Física En La Escuela Primaria De Tasikmalaya, Indonesia (Instrument for Assessing Physical Literacy Skills Competence in Primary School Tasikmalaya, Indonesia) - Permana, Rahmat; Isti'adah, Feida Noorlaila; Dewi, Rikha Surtika; Nurkamilah, Milah; Fitri, Sulidar; Nofrizal, Dedi; Purba, Pangondian Hotliber; Pranata, Didi Yudha; Sari, Liliana Puspa; S, Adi (Retos, 2024)
This study aims to conceive, develop and evaluate the validity of a Physical Literacy (PL) instrument designed for primary school students in Tasikmalaya, Indonesia. Children between the ages of 8 and 12 will constitute a sample for this development research project. The validity of the instrument was assessed through the analysis of the alpha coefficient, and the results were quite good. All items have alpha coefficients close to or equal to 1.00, which indicates that the validation instrument is intended to be valid. Once it allows you to classify students according to their levels of ability and perform more effective assessments in the domain of physical education, PL assessment is necessary for physical education teachers and for school teachers. The planning of the physical education curriculum focuses more on physical literacy; Each student needs to be bettered to be easier with this instrument. Therefore, this assessment instrument is beneficial for teachers to obtain a record of individual and collective progress of students in physical education learning. The results of this study show that the instrument created is reliable and successfully collected PL data in the city of Tasikmalaya, in Indonesia. Once we can ensure that the efforts of the trainers are focused on the specific needs of each student through the use of the PL assessment instrument, we will obtain more significant results in the PL of the primary school students. Keywords: Physical literacy, Avaliação, Basic education, Skills competence Summary. This study aims to conceive, develop and evaluate the validity of a physical literacy (PL) instrument designed for primary school students in Tasikmalaya, Indonesia. Children between the ages of 8 and 12 will constitute a sample for this development research project. The validity of the instrument was assessed through the analysis of the alpha coefficient, and the results were quite good. All items have alpha coefficients close to or equal to 1.00, which indicates that the validation instrument is intended to be valid. Once it allows you to classify students according to their levels of ability and carry out more effective physical education assessments, physical education teachers and school teachers need a PL assessment. The planning of the physical education curriculum concentrates more on physical literacy; Each student needs to be bettered to be simpler with this instrument. Therefore, this assessment instrument is beneficial for teachers in obtaining a record of individual and collective progress of students in physical education learning. The results of this study show that the instrument created is reliable and successfully collected PL data in the city of Tasikmalaya, located in Indonesia. Once we can ensure that training efforts are concentrated on the specific needs of each student through the use of the PL assessment instrument, we will obtain more significant results in PL for primary school students.